Tathbiq Was?lah Bi??q?t Mu?awwarah Li-Ta?s?n Itq?n al-Mufrad?t al-?Arabiyyah li-?alabat a?-?aff as-S?bi? bi al-Madrasah ath-Th?nawiyyah N?r al-?ikmah T?l?da M?l?ngki L?w? ash-Sham?liyah - Syamsuddin, Naidin; Nurmiati, Nurmiati; Rosdeviana, Rosdeviana (Al Ibrah: Journal of Arabic Language Education, 2023)
AbstractThis study examines the application of picture cards to improve the Arabic vocabulary proficiency of seventh grade students at Noor El Hikma Preparatory School, Tolada, North Malangki. Kimis and McTaggart's working research approach was used to monitor the effectiveness of this method in two educational sessions. The results of the study showed that the application of photo cards was effective in improving students' mastery of Arabic vocabulary. This is proven by significantly increasing the average score and level of completion of vocabulary exercises in each course. In the second cycle, 100% of students achieved a minimum completion score of 70%, demonstrating excellent vocabulary proficiency. These results show that picture cards can be a useful educational tool to improve Arabic vocabulary learning, especially for students who have difficulty with traditional educational methods.. Keywords: Teaching aid, Ficture Cards, Arabic Vocabulary.???????? ??? ??????? ????? ?????? ????? ?????? ????? ???????? ??????? ??? ???? ???? ?????? ?? ????? ??? ?????? ?????????? ??????? ???????? ????????. ?? ??????? ??? ??? ????? ?? ????? ???? ?????? ??????? ?????? ??? ??????? ?? ?????? ?????????. ????? ????? ??????? ?? ????? ?????? ????? ??? ?????? ?? ????? ????? ?????? ???????? ???????. ??? ??? ?? ???? ????? ????? ??????? ?????? ????? ?????? ???????? ???? ???? ?? ?? ????. ?? ?????? ???????? ??? 100% ?? ?????? ?????? ??????? ?????? ????? 70%? ??? ??? ??? ????? ????? ????????. ???? ??? ??????? ?? ?????? ????? ???? ?? ???? ???? ??????? ????? ?????? ???? ???????? ???????? ????? ?????? ????? ????? ????? ?? ???????? ????????? ????????? .  ??????? ?????????: ????? ???????? ?????? ?????? ???????? ???????.